Análisis del guion técnico y literario de las películas: Mejor no hablar de ciertas cosas; Tan distintos; Saudade, Solo es una más; y, Con alas para volar. - Sánchez Salinas, Darío Javier (2021)
Ecuadorian cinema has developed more strongly over the last twenty years, and this development is due to several factors, including the specialization of directors and technical teams, and competitive funds for audiovisual projects. In this context, it is important to identify the elements and characteristics that audiovisual productions present in the literary and technical scripts to achieve the attention and empathy of the public. The box office of Ecuadorian cinema is low in relation to foreign cinema, generally the economic investment in film production is not recovered at the box office. To analyze the characteristics of the script, we used a mixed methodology, in which the five highest-grossing films between 2013 and 2017 were analyzed, we determined the recurring resources in script that allowed generating closeness and empathy with the audience. To complement the research, semi-structured interviews were conducted with the directors and screenwriters of each film. From the results obtained we can conclude that in the analyzed films the directors seek to generate empathy with the audience through introspective and realistic scripts. Regarding the image, Ecuadorian cinema does not have high budgets, so directors use natural resources and image level; movements and framing are similar due to economic limitations. As a result of this research, as an alternative proposal, a blog was created, in which the cinematographic technical elements can be evidenced, this to promote an audiovisual culture in order to promote audiovisual producers to generate products with a better knowledge of the field.